2005
DOI: 10.1093/schbul/sbj050
|View full text |Cite
|
Sign up to set email alerts
|

Review of Clinical Correlates of P50 Sensory Gating Abnormalities in Patients with Schizophrenia

Abstract: A large percentage of patients with schizophrenia are characterized by an abnormality in P50 sensory gating. This abnormality has been shown to be genetically linked to the alpha-7 nicotinic receptor and is transiently reversed by acute nicotine administration. These observations have led to the development of pharmacological treatments designed to improve sensory gating. However, if normalization of P50 gating abnormalities is to guide drug development, then it becomes important to delineate the clinical corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(162 citation statements)
references
References 58 publications
8
152
1
1
Order By: Relevance
“…P50 inhibition also improved. More detailed information on this area is available in several recent reviews (Levin, 2002;Martin et al, 2004;Potter et al, 2006).…”
Section: Alpha7nachr and Information Processingmentioning
confidence: 99%
“…P50 inhibition also improved. More detailed information on this area is available in several recent reviews (Levin, 2002;Martin et al, 2004;Potter et al, 2006).…”
Section: Alpha7nachr and Information Processingmentioning
confidence: 99%
“…Three studies investigated differential psychopharmacological effects with measures of central inhibition or gating: prepulse inhibition (PPI) of the acoustic startle response and suppression of the P50 event-related potential in a condition-test paradigm (P50 gating) (Csomor et al 2008;Knott et al 2010;Vollenweider et al 2006). Both gating processes provide the individual with the ability to negotiate a sensory-laden environment by blocking out excess or trivial stimuli so that an individual can focus attention on the most salient aspects of the stimulusladen environment (Braff et al 2001;Potter et al 2006). Vollenweider et al (2006) demonstrated that the antipsychotic clozapine significantly increased PPI levels in low PPI performers but showed no effect in high PPI performers.…”
mentioning
confidence: 99%
“…This is said to be indicative of sensory gating: cerebral activity is maintained towards the first stimulus until neurological processing of it has been completed. Potter et al (2006) also describe sensory gating as "…the pre-attentional habituation of responses to repeated exposure to the same sensory stimulus." The fact that both people who suffer from schizophrenia and their first-degree relatives show a lack of pre-pulse inhibition demonstrates a possible liability to this illness.…”
Section: Sensory Gating In Schizophreniamentioning
confidence: 99%